Equine de-worming: a consensus on current best practice. (1st January 2019) - Rendle, David; Austin, Corrine; Bowen, Mark; Cameron, Ian; Furtado, Tamzin; Hodgkinson, Jane; McGorum, Bruce; Matthews, Jacqueline
Abstract : Despite increasing awareness within the veterinary profession and equine industry of the potential implications of anthelmintic resistance (AHR), there is a concern that insufficient measures are being taken to reduce its development and spread. This document was commissioned to provide veterinary surgeons with up to date information on worm control plans that will prevent clinical disease while minimising selection pressure for resistance. Recommendations were developed using an informal two-round Delphi process, considering published and unpublished research relating to equine parasite control using a roundtable forum and online discussion. Where research evidence was conflicting or absent, collective expert opinion, based on the experience of the group, was applied. The opinions expressed are the consensus of views expressed by the authors. Where agreement was not reached opposing views are presented such that readers can understand the arguments. The document is focused on the management of horses and ponies; while much of the information herein applies to donkeys, it is important to recognise that donkeys face major challenges with AHR, and further research is required before specific recommendations can be made with respect to this species. The expert group was organised by UK-Vet Equine and hosted by Moredun Research Institute with sponsorship from Virbac and additional support from The Horse Trust and vetPartners.